PENDIDIKAN KARAKTER ANAK DALAM KELUARGA DISHARMONI DI KECANDRAN SALATIGA - zumrotul zum; Muchamad Chairul Umam (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2021)
Abstract                                      Character education for children in the family is basically given as early as possible so that character education is carried out from the simplest habits to be complex. The charecter education is effectively given through habituation. The method of educating children by growing love for them is now believed to be accurate children by growing love for them is now believed to accurate in the modern world. This turned out to have been applied by the telada of Muslims, Rasulullah SAW. Disharmony families are conditions where families cannot carry out their functions and roles so that each family member fails to carry out their obligations. Disharmony family is a family life whose members are still complete in structure but in the family members there is lack of attention, lack of communication, family members have their respective activities and costant fights between fathers and mothers that can bring family divorce. The purpose of character education in disharmony families in Kecandran Salatiga is different. The goal and expectation of parents to their children are always good and want their children to be good personal, religious and can respect other religious adherents. The material taught by parents relates to parents espectations, usually about good advice and good Islamic teachings. How to educate children in accordance with 18 character values through the exemplary method, the method of advice and the provision of punishment. Evaluation of character testing is done by testing the level honesty. The constraints of character education of childran in disharmony families in Kecandran Salatiga. Firs, parents must always remind their children because their children and have problems in learning that is difficults in capturing subject metter. Second, addressing children who are spoiled and lazy to learn. Third, namely the child still often asks on of his parents while there are various kinds of economic problems.